RATIONAL APPLICATION OF HUMAN NORMAL IMMUNOGLOBULIN FOR THE INTRAVENOUS INDUCTION - I.D. Fesenko (Педиатрическая фармакология)
Intravenous induction of human normal immunoglobulin is widely applied to treat various diseases; this is a highly effective and rather a safe treatment approach. According to the findings of the randomized controlled tests, the effectiveness of the given group of medications was proved in a number of immunopathologic states. On the other hand, sometimes the range of diseases, during which human normal immunoglobulin is applied, has groundlessly been extended of late. The article highlights the modern data about the contents, indications, mechanisms of impact, frequency and types of adverse reactions to the induction of human normal immunoglobulin, as well as the data about relative effectiveness of different medications.Key words: human normal immunoglobulin, adverse reactions, children.